Pengaruh Faktor-Faktor Individual dan Institusional Terhadap Kepatuhan Wajib Pajak Restoran - Mahmuda, Annisa Rahma; Mustofa, Rasyid Mei; Kusuma, Poppy Dian Indira (Unand Press, 2019)
This study aims at providing explanation of how tax audit, cash availability, perceived benefit, trust in government, and moral responsibility affects tax compliance. Those factors are predicted to direct tax compliance behavior. A survey involving 73 restaurant owners was conducted to gather data. Using multiple regression analysis, the results show that tax audit, perceived benefit, trust in government, and moral responsibility positively affect tax compliance. Meanwhile, cash availability has no effect on tax compliance. These results imply that to have tax payers’ compliance, several actions should be undertaken by government. Among those actions are improving tax audit and tax payers’ trust. In addition, government also has to improve tax fund allocation to bring better benefits to tax payers. Socialitation is also significant to improve tax payers’ moral responsibility and motivation to comply.